2022
DOI: 10.3390/antibiotics11020194
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis for Hepato-Biliopancreatic Surgery—A Systematic Review

Abstract: Background: Surgical site infections (SSIs) are among the most important determinants of morbidity after HBP surgery. Their frequency after HPB surgery is variable, from 1–2% after elective cholecystectomy to 25% after PD. Methods: A systematic review was performed to assess the role of antimicrobial prophylaxis (AP) in HPB elective surgery. Articles published between 2015 and 2021 were obtained; those before 2015 were not included because they antedate the WHO guidelines on SSI prevention. We conducted three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…To determine the effect of antibiotics on detection of S. Typhi in bile by either culture or qPCR, we carried out several spiking experiments. Bile samples were spiked with S. Typhi and one of three cephalosporins, cefazolin, cefotaxime, or ceftriaxone, that are commonly administered parenterally to patients just prior to undergoing cholecystectomy to diminish surgical wound infections ( 18 ). Samples were then processed for qPCR or cultured in broth.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effect of antibiotics on detection of S. Typhi in bile by either culture or qPCR, we carried out several spiking experiments. Bile samples were spiked with S. Typhi and one of three cephalosporins, cefazolin, cefotaxime, or ceftriaxone, that are commonly administered parenterally to patients just prior to undergoing cholecystectomy to diminish surgical wound infections ( 18 ). Samples were then processed for qPCR or cultured in broth.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatobiliopancreatic surgery encompasses a wide array of procedures aimed at treating disorders of the liver, bile ducts, and pancreas, ranging from benign to malignant conditions [ 9 , 25 ]. Despite significant advancements in surgical techniques and perioperative care, this field remains inherently complex and challenging [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, similar occurrences to those detailed in the current investigation, involving Gram-negative microorganisms such as Enterobacteriaceae , as well as Gram-positive microorganisms including Enterococcus , have been previously documented [ 14 , 15 ]. However, past microbiological investigations have indicated a heightened prevalence of Enterococcus species (52%) and a similar occurrence of K. pneumoniae (23%) [ 25 ]. It is important to highlight that local geographic differences in the prevalence of microorganisms have been recognized [ 12 , 26 , 27 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other prior studies elaborated that extended antibiotic use was correlated with the reduced incidence rate of SSIs following PD in high-risk patients [18,19] . On the contrary, a systematic review illustrated that a single preoperative dose of cefazolin for hepato-biliopancreatic surgery is indicated for AP [17] . In our study, we revealed an insigni cant correlation between all types of SSIs and other HAIs with postoperative AP after adjustment for the risk factors of patients, which supports the Chinese guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the Chinese Guidelines for Clinical Use of Antibiotics [16] classi ed that the duration of AP after clean-contaminated surgery and contaminated surgery should not exceed 24 hours and might extend to 48 hours for contaminated surgery when necessary. A recent study elucidated that one preoperative antibiotic dose might be adequate for surgical prophylaxis in patients undergoing pancreatic surgery [17] . However, Fromentin et al [18] and Hammad et al [19] reported that extended AP could reduce the incidence of SSI among high-risk patients.…”
Section: Introductionmentioning
confidence: 99%